Redes de coautoria em Ciência da Informação no Brasil: dinâmica na produção científica dos atores mediada pela ANCIB - Alzira Karla Araújo da Lima (2012)
Co-authorship networks constitute strategies to share information and knowledge by scientific communities. In this context, the present research analyzes the dynamics of co-authorship networks in the field of Information Science. It identifies the actors and the scientific production about organization and representation of knowledge (ORK). Moreover, it characterizes the most productive actors in relation to their gender, academic formation, institutional linkage, and geographic region. Also, it reveals the interinstitutional and intrainstituional co-authorship networks. The research characterizes the nature of relations among co-authors in relation to guidance linkages and of research group members. It presents measures of social cohesion, of periphery and of cluster. In addition, the descriptive and documental research with qualitative and quantitative approach is adopted. It uses triangulation of data when it adopts formularies while worksheets and software to the collection and triangulation of methods are used in the quantitative and qualitative approach. The field research is the scientific production of ORK of the Brazilian Association of Research in Information Science (ANCIB) during twelve editions of the National Meeting of Research in Information Science (ENANCIB). The population is constituted by authors of the works about ORK that were published in these annals. The data sources are the annals of ENANCIB, Lattes Curriculum, and the CNPq Group Directory of the authors (actors) and their co-authors. It uses the modeling of social networks and of representation in graphs, worksheets and formularies, Pajek software and the social network analysis (SNA) to structure and analyze the collected data. The most relevant results indicated that, in the studied period, 294 works of 297 authors, affiliated to 60 institutions were presented at WG2/ENANCIB. From this role, 25 constitute the most productive actors, who are responsible for a significant portion of works, most of them were elaborated in co-authorship. The institutions represented by the most productive actors are in the Southeast Region of Brazil. The linkage of these actors is concentrated at the Federal University of Minas Gerais (UFMG), São Paulo State University (UNESP) and University of São Paulo (USP). Most of the actors established mixed connections, of interinstitutional and intrainstitutional nature. The study permitted to conclude that the formation of co-authorship networks promotes interaction and collaboration among researchers and it can contribute to generate new relations, knowledge and scientific production. However, it is believed that these networks can include new actors, national and international institutions and to promote more interinstitutional connections.